Controlling the bioactivity of a peptide hormone in vivo by reversible self-assembly - Myriam M. Ouberai (Nature Portfolio, 2017)
The clinical potential of peptide therapeutic agents can only be fully realised once their physicochemical and pharmacokinetic properties are precisely controlled. Here the authors show a reversible peptide self-assembly strategy to control and prolong the bioactivity of a native peptide hormone in vivo.